Antimicrobial Activity Comparison Profile of Piper betle L., Pluchea indica L. and Citrus aurantifolia [Christm.] Swingle against Bacterial Isolates from Human Axillary Sweat with Odor Problem - Nur Miftahurrohmah; Syarmalina Syarmalina (School of Pharmacy Institut Teknologi Bandung, 2013)
The research to compare the antimicrobial activity profile of Piper betle L. leaf, Pluchea indica L. leaf, and Citrus aurantifolia [Christm.] Swingle fruit against bacteria isolated from axillary sweat of six probandus having axillary odor problem had been done. Eight pure bacterial isolates came from this process, and then identified with Gram stain and several biochemical reactions. Staphylooccus aureus, S. epidermidis, and S. haemolyticus, known as bacteria that usually present in a large amount at human axilla skin with odor problem, were used also in this research. The tested plants were prepared with procedures that usually used by the Indonesian people as traditional home medicine to face the axillary odor problem. Furthermore, fucidic acid and potassium alumunium phosphate were used as reference drugs. Antimicrobial activity of all of the plants and the reference drugs against 11 bacteria were studied using agar diffusion method. The results showed that liquid extracted from Citrus aurantifolia [Christm.] Swingle. fructus had the highest antimicrobial activity compared to the two other plants against bacteria isolated from axillary sweat with odor problem, which was equal with the antimicrobial activity of potassium alumunium phosphate 20% w/v solution. Antimicrobial activity of betel leaf and beluntas leaf were equal with the antimicrobial activity of 19.06 Î¼g/mL of fusidic acid solution.Keywords: betel leaf, Piper betle L., beluntas leaf, Pluchea indica L., lime fruit, Citrus aurantifolia [Christm.] Swingle, antimicrobial, axillary odor. AbstrakTelah dilakukan penelitian untuk membandingkan aktivitas antimikroba dari daun sirih (Piper betle L.), daun beluntas (Pluchea indica L.), dan buah jeruk nipis (Citrus arantifolia [Christm.] Swingle) terhadap bakteri yang diisolasi dari keringat ketiak enam sukarelawan yang memiliki masalah bau ketiak. Delapan isolat bakteri murni didapat dari proses ini dan kemudian diidentifikasi dengan pewarnaan Gram dan uji-uji biokimia. Bakteri Staphylooccus aureus, S. epidermidis, dan S. haemolyticus yang umumnya terdapat dalam jumlah banyak di kulit ketiak yang berbau juga digunakan dalam penelitian ini. Tanaman-tanaman uji disiapkan dengan cara yang biasa dilakukan oleh masyarakat Indonesia untuk mengatasi bau badan secara tradisional. Sebagai senyawa antimikroba standar, digunakan asam fusidat dan tawas (kalium aluminium fosfat) untuk dibandingkan aktivitasnya dengan tiga tanaman uji. Aktivitas antimikroba seluruh tanaman uji dan larutan senyawa antimikroba terhadap 11 bakteri diteliti dengan menggunakan metode difusi agar. Hasil uji menunjukkan bahwa air perasan jeruk nipis memiliki aktivitas antimikroba terbesar dibandingkan dengan dua tanaman uji lainnya terhadap bakteri yang diisolasi dari keringat ketiak yang berbau, yang sebanding dengan aktivitas antimikroba larutan tawas 20% b/v. Aktivitas antimikroba daun sirih dan daun beluntas sebanding dengan aktivitas antimikroba larutan asam fusidat 19,06 Î¼g/mL.Kata kunci: sirih, Piper betle L., beluntas, Pluchea indica L., jeruk nipis, Citrus aurantifolia [Christm.] Swingle, antimikroba, bau ketiak.